2005
DOI: 10.1176/appi.ajp.162.5.1005
|View full text |Cite
|
Sign up to set email alerts
|

Association of Genetic Variants in Alcohol Dehydrogenase 4 With Alcohol Dependence in Brazilian Patients

Abstract: Objective:The authors evaluated the association of three functional promoter polymorphisms of the ADH4 gene with alcohol dependence.Method: DNA from 92 alcohol-dependent patients and 92 healthy comparison subjects was genotyped for all three polymorphisms.Results: Variants at the -75 base-pair (bp) (C allele) and -159 bp (A allele) positions were associated with alcohol dependence. Individuals with haplotypes carrying both risk alleles showed an odds ratio of 2.9. Conclusions:These preliminary results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
52
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 11 publications
5
52
0
Order By: Relevance
“…Recently, several genes have been associated with the risk for alcoholism, including GABRA2 (Covault et al, 2004;Edenberg et al, 2004;Fehr et al, 2006;Lappalainen et al, 2005), ADH4 Guindalini et al, 2005;Luo et al, 2005b), and CHRM2 (Luo et al, 2005a;Wang et al, 2004), and their role in alcoholism susceptibility has been confirmed in multiple studies. Additional genes have also been implicated in disease risk, including GABRG3 ) and a bitter taste receptor, TAS2R16 (Hinrichs et al, 2006).…”
mentioning
confidence: 96%
“…Recently, several genes have been associated with the risk for alcoholism, including GABRA2 (Covault et al, 2004;Edenberg et al, 2004;Fehr et al, 2006;Lappalainen et al, 2005), ADH4 Guindalini et al, 2005;Luo et al, 2005b), and CHRM2 (Luo et al, 2005a;Wang et al, 2004), and their role in alcoholism susceptibility has been confirmed in multiple studies. Additional genes have also been implicated in disease risk, including GABRG3 ) and a bitter taste receptor, TAS2R16 (Hinrichs et al, 2006).…”
mentioning
confidence: 96%
“…Nevertheless, several genes have been associated with a risk for alcoholism in studies that have been replicated, e.g. GABRA2 (Covault et al, 2004;Edenberg et al, 2004;Fehr et al, 2006;Lappalainen et al, 2005), ADH4 Guindalini et al, 2005;Luo et al, 2005a), and CHRM2 (Luo et al, 2005b;Wang et al, 2004). It is evident, however, that there are other genes that also influence the risk for alcoholism.…”
mentioning
confidence: 99%
“…The presence or absence of Gene × Environment interactions may be partially related to differences in the strength of the associations of the ADH variants with alcohol dependence. The current evidence is inconsistent for the association of rs1800759 with alcohol-related phenotypes (Edenberg et al, 2006;Guindalini et al, 2005;Luo et al, 2005;Preuss et al, 2011), suggesting a weaker association for this variant. In our study, rs1229984 showed evidence of a main-effect-only relationship with maximum drinks and alcohol dependence symptoms.…”
Section: Discussionmentioning
confidence: 81%
“…Edenberg et al (1999) reported that the ADH4-rs1800759 C allele has lower promoter activity than the A allele, suggesting a greater risk for alcohol dependence for C allele carriers. Rs1800759 has been associated with alcohol dependence in some samples (Guindalini et al, 2005;Luo et al, 2006;Preuss et al, 2011) but not in others (Edenberg et al, 2006;Luo et al, 2005). This could be because of differences in the characteristics for the samples studied (e.g., case-control samples recruited from clinical populations versus familybased samples; Preuss et al, 2011).…”
mentioning
confidence: 99%